2018
DOI: 10.15252/embr.201745336
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA s based on huntingtin trinucleotide repeats are highly toxic to cancer cells

Abstract: Trinucleotide repeat (TNR) expansions in the genome cause a number of degenerative diseases. A prominent TNR expansion involves the triplet CAG in the huntingtin (HTT) gene responsible for Huntington's disease (HD). Pathology is caused by protein and RNA generated from the TNR regions including small siRNA-sized repeat fragments. An inverse correlation between the length of the repeats in HTT and cancer incidence has been reported for HD patients. We now show that siRNAs based on the CAG TNR are toxic to cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…To test whether certain 6mer seeds present in the guide strand of an siRNA affect cancer cell survival, we recently designed a neutral 19mer oligonucleotide scaffold with two nucleotide 3′ overhangs, and we demonstrated that modifying an siRNA strand at positions 1 and 2 by 2′- O -methylation (OMe) completely blocks its loading into the RISC 22 . Different 6mer sequences can be inserted at positions 2–7 of the guide strand with the designated passenger strand modified by OMe (two red Xs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether certain 6mer seeds present in the guide strand of an siRNA affect cancer cell survival, we recently designed a neutral 19mer oligonucleotide scaffold with two nucleotide 3′ overhangs, and we demonstrated that modifying an siRNA strand at positions 1 and 2 by 2′- O -methylation (OMe) completely blocks its loading into the RISC 22 . Different 6mer sequences can be inserted at positions 2–7 of the guide strand with the designated passenger strand modified by OMe (two red Xs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although there is some evidence that there is reduced cancer in HD, this is not a hard-and-fast rule, since it appears to depend on the type of cancer involved 66 . Most recently, there is evidence that CAG/CUG repeats may be toxic to cancer cells 11 . This raises the intriguing possibility that CAG repeats are part of a natural defence mechanism against tumours.…”
Section: Discussionmentioning
confidence: 99%
“…There is both direct and indirect evidence to support this idea 68 . More recently, the idea of antagonistic pleiotropy in HD re-emerged, with new evidence showing that there is a reduced incidence of cancer in HD patients 9,10 and that small interfering (si) RNAs based on the HD gene are toxic to cancer cells 11 . If HTT is an example of a gene showing antagonistic pleiotropy, then this may explain, at least in part, why HD persists in the population despite its eventual devastating effects on the individual.…”
Section: Introductionmentioning
confidence: 99%
“…CAG-repeat-containing mRNAs have been shown to induce sRNA formation and cellular toxicity via RNAi ( Bañez-Coronel et al, 2012 ). However, we recently reported that these sCAGs likely target fully complementary CUG containing repeat regions in the ORFs of genes critical for cell survival in an siRNA-like mechanism ( Murmann et al, 2018a ; Murmann et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…These eight siRNAs were reverse transfected into HeyA8, H460, M565, and 3LL cells using RNAiMAX transfection reagent (ThermoFisher Scientific) at 10 nM in triplicate as previously described ( Murmann et al, 2018a ). The non-targeting (NT) and siL3 siRNAs, as described previously ( Putzbach et al, 2017 ), were used as a negative and positive control, respectively.…”
Section: Methodsmentioning
confidence: 99%